(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
The first method by micellar electrokinetic chromatography (MEKC) for the determination of empagliflozin in tablets was developed and validated following the ICH guidelines. The separation was achieved in a fused silica capillary with 50 µm x 40 cm (inner diameter x effective length) at 28 ºC, +28 kV voltage, hydrodynamic injection 4s (50 mBar), detection at 225 nm and paracetamol was the internal standard. The running electrolyte was a mixture of 20 mM tris(hydroxymethyl) aminomethane (pH 10) and 100 mM sodium dodecyl sulphate (1:1). Specificity was evaluated by the stress testing and the method was specific, with no interference of the degradation product. Linearity was observed in the range of 50 to 150 μg/mL (r=0.9999). The method showed adequate accuracy (recovery value=100.60±0.60%), precision (RSD values <2%) and robustness, which was evaluated by a full factorial design 23. Drug degradation kinetics was evaluated in alkaline andacidic conditions and first-order kinetic was observed in both conditions. The cytotoxicity of sample solutions degraded by UVA and UVC radiation, alkaline and acid media were studied as well. A similar cellular viability profile was observed with a slight decrease only in samples degraded by UVC radiation and basic medium.